Ethnobotanical investigation of Baccaurea spp. (Phyllantaceae) used by local people near Gunung Leuser National Park, Aceh, Indonesia - Zidni Ilman Navia; Adi Bejo Suwardi; Tisna Harmawan (Ethnobotany Research and Applications, 2022)
Background: Baccaurea spp. is a fruit species that grows in Gunung Leuser National Park and has long been used for food by local communities in the nearby forest. Moreover, several Baccaurea spp. are underutilized. Population growth in and near forested areas accelerates forest degradation and threatens the existence of Baccaurea spp. in the wild. This study aims to investigate the diversity, use, and role of traditional knowledge in the conservation of Baccaurea spp. in Gunung Leuser National Park, Aceh, Indonesia. Methods: This study was carried out in 12 villages from 6 sub-districts and 4 districts in Aceh province. Extensive field surveys, plant collection, and interviews with local communities were used in this study. The exploration method was used to gather Baccaurea spp. samples. Identification of Baccaurea specimens is accomplished through the use of identification keys, comparison with previously identified herbarium specimens, and/or confirmation with relevant taxa experts. Semi-structured interviews with 390 randomly selected respondents were used to collect ethnobotanical data on the use of Baccaurea spp. Results: A total of nine Baccaurea spp. were identified, with 90% growing wild in the forest. Baccaurea polyneura was the most preferred species for local communities in the study area. Local communities have used Baccaurea spp. for different purposes, including food, medicine, construction material, agricultural tools, fodder, and fuelwood. More than 60% of traditional knowledge related to the use of Baccaurea spp. was obtained from their relatives. Conclusion: A total of ten Baccaurea spp. were discovered in the study area. Baccaurea spp. also plays an important role as a source of medicine, construction material, agricultural tools, fodder, and fuelwood, as well as for food. Baccaurea spp., however, in the study area is threatened by several factors, mainly agricultural expansion, implying that conservation efforts should be improved with the implementation of sustainable management strategies based on traditional knowledge that prioritizes Baccaurea species frequently used by local communities. Keywords: Baccaurea, edible fruit, traditional knowledge, GLNP, Aceh Abstrak Latar Belakang: Baccaurea merupakan tumbuhan penghasil buah yang tumbuh di kawasan Taman Nasional Gunung Leuser dan sejak lama telah dimanfaatkan oleh masyarakat sekitar hutan, terutama sebagai bahan makanan. Meskipun demikian, beberapa Baccaurea spp. masih belum dimanfaatkan. Pertumbuhan populasi penduduk di sekitar hutan mendorong peningkatan degradasi hutan dan mengancam kelestarian Baccaurea spp. di alam. Penelitian ini bertujuan untuk mengkaji keanekaragaman, pemanfaatan, dan peran pengetahuan tradisional dalam konservasi Baccaurea spp. di Taman Nasional Gunung Leuser, Aceh, Indonesia. Metode: Penelitian ini dilakukan di 12 desa dari 6 kecamatan dan 4 kabupaten di Provinsi Aceh melalui survei lapangan, koleksi tumbuhan, dan wawancara dengan masyarakat lokal. Metode eksplorasi digunakan untuk mengumpulkan spesimen Baccaurea spp. Identifikasi spesimen Baccaurea spp. dilakukan menggunakan kunci identifikasi, perbandingan dengan spesimen herbarium yang telah diidentifikasi sebelumnya, dan/atau konfirmasi dengan ahli taksa terkait. Wawancara semi-terstruktur dengan melibatkan 390 responden yang dipilih secara acak digunakan untuk mengumpulkan data etnobotani tentang pemanfaatan Baccaurea spp. Hasil: Sebanyak 10 spesies Baccaurea spp. telah ditemukan di lokasi penelitian, dengan 90% diantaranya tumbuh liar di hutan. Baccaurea polyneura merupakan jenis tumbuhan yang paling disukai oleh masyarakat lokal di lokasi penelitian. Masyarakat lokal telah memanfaatkan Baccaurea spp. untuk berbagai keperluan, seperti makanan, obat-obatan, bahan bangunan, alat pertanian, pakan ternak, dan kayu bakar. Lebih dari 60% pengetahuan tradisional terkait pemanfaatan Baccaurea spp. diperoleh dari orang tua mereka. Kesimpulan: Sebanyak 10 jenis Baccaurea spp. telah ditemukan di lokasi penelitian. Baccaurea spp. berperan penting bagi kehidupan masyarakat sekitar hutan terutama dimanfaatkan sebagai makanan, obat-obatan, bahan bangunan, alat pertanian, pakan ternak, dan kayu bakar, serta untuk pangan. Meskipun demikian, Baccaurea spp. di lokasi penelitian terancam oleh beberapa faktor, terutama perluasan lahan pertanian, yang menyiratkan bahwa upaya konservasi perlu ditingkatkan melalui penerapan strategi pengelolaan berkelanjutan berbasis pengetahuan tradisional dengan memprioritaskan jenis Baccaurea yang sering dimanfaatkan oleh masyarakat lokal. Kata kunci: Baccaurea, buah edibel, pengetahuan tradisional, TNGL, Aceh